Research and information for sustainable forests - Sayer, Jeffrey A. (1998)
Forestry is no longer just about ensuring sustained supplies of timber, non-timber products and wildlife, today a much wider range of local, regional and global values influence decisions on how to manage forests. Forests are central to debate on climatic change, water management and biodiversity conservation. Progress in information technology allowing manipulation of complete data sets, computer-based models and remote sensing capabilities are all contributing to providing the information which is now needed to manage forests. As economics are liberalised and trade barriers reduced forests are becoming more and more a global resource. Decisions formerly made by government forest agencies are increasingly being made by corporate investors. The implications for research are that the private sector will dominate areas such as tree improvement, plantation technology and wood processing but will not find it attractive to invest in research about the public-good values of forests. It will be important for the public sector to engage in research, which provides the ability to assess a variety of forest conditions, monitor changes and develop standards against which to evaluate forest management practices. The paper poses questions on the provision of scientific advice to the Intergovernmental Forum on Forests; what form an international consultative mechanism for forest research should take, identification of new collaborative initiatives and the way forward for initiatives for global forest information systems.